How much emergency department use by vulnerable populations is potentially preventable?: A period prevalence study of linked public hospital data in South Australia. Issue 1 (17th January 2019) - Banham, David; Karnon, Jonathan; Densley, Kirsten; Lynch, John W
Abstract : Objectives: To quantify emergency department (ED) presentations by individuals within vulnerable populations compared with other adults and the extent to which these are potentially preventable. Design: Period prevalence study from 2005-2006 to 2010–2011. Setting: Person-linked, ED administrative records for public hospitals in South Australia. Participants: Adults aged 20 or more in South Australia's metropolitan area presenting to ED and categorised as Refugee and Asylum Seeker Countries of birth (RASC); Aboriginal; those aged 75 years or more; or All others. Main outcome measures: Unadjusted rates of ambulatory care sensitive condition (ACSC), general practitioner (GP)–type presentations and associated direct ED costs among mutually exclusive groups of individuals. Results: Disparity between RASC and All others was greatest for GP-type presentations (423.7 and 240.1 persons per 1000 population, respectively) with excess costs of $A106 573 (95% CI $A98 775 to $A114 371) per 1000 population. Aboriginal had highest acute ACSC presenter rates (125.8 against 51.6 per 1000 population) with twice the risk of multiple presentations and $A108 701 (95% CI $A374 to $A123 029) per 1000 excess costs. Those aged 75 or more had highest chronic ACSC presenter rates (119.7vs21.1 per 1000), threefold risk of further presentations (incidence rate ratio 3.20, 95% CI 3.14 to 3.26) and excess cost of $A385 (95% CI $A178 160 to $A184 609) per 1000 population. Conclusions: Vulnerable groups had excess ED presentations for a range of issues potentially better addressed through primary and community healthcare. The observed differences suggest inequities in the uptake of effective primary and community care and represent a source of excess cost to the public hospital system.